Gardenstay design: towards sustainable Royal City of Muar Johor - Abas, Siti Aisah; Kamarul Zaman, Hudaa Mardhiyah; Mohd Paruddin, Nir Faezah; Amran, Nurul Fatiha; Sarifuddin, Farah Najwa; Khairi, Nadiah (2021)
Community-Based Tourism Initiatives (CBTI) has become one of the government's continuous efforts and support to the local community empowerment through their participation in tourism activities. In addition, the government also committed to providing education and training for those who involve in homestay programs before they start with physical development or creating, packages for the potential tourists. In line with the Sustainable Development Goals (SDCs), Gardenstay Design in which incorporates the nursery homestay concept could be a potential new tourism product that promotes awareness of sustainable city's landscape in Sabak Awor located in the Royal City of Muar. Sabak Awor is considered the oldest village in Muar. It was formerly discovered by a group of settlers who explored Sungai Muar in the year 1850. Currently, Sabak Awor was surrounded by so many nurseries, natural attractions and most of the local community has been ready to be involved in this program. By using Unique Selling Proposition (USP), Gardenstay Design is unique in which integrated three elements comprise traditional food, interpretive walk, and terrarium concept. Tourists would enjoy the exclusive meal of venison throughout their stay. This is considered the unique proposition of Sabak Awor because the deer are cattle in Sabak Awor by locals residents. Moreover, the interpretive walk is an initiative that integrates the selected potential business to expose the tourists to the experience of 'kampung vibe'. Next, tourists would get the chance to decorate their own mini-gardens through this activity of making terrariums. In a nutshell, the Gardenstay Design would contribute to local empowerment, promote awareness of sustainable homestay programs, and indirectly will boost up tourist arrival to Muar as one of the sustainable tourist destinations in the future.